Isatin Bis-Imidathiazole Hybrids Identified as FtsZ Inhibitors with On-Target Activity Against Staphylococcus aureus - Rita Morigi; Daniele Esposito; Matteo Calvaresi; Tainah Dorina Marforio; Giovanna Angela Gentilomi; Francesca Bonvicini; Alessandra Locatelli (MDPI AG, 2024)
In the present study, a series of isatin bis-imidathiazole hybrids was designed and synthesized to develop a new class of heterocyclic compounds with improved antimicrobial activity against pathogens responsible for hospital- and community-acquired infections. A remarkable inhibitory activity against Staphylococcus aureus was demonstrated for a subset of compounds (range: 13.8-90.1 µM) in the absence of toxicity towards epithelial cells and human red blood cells. The best performing derivative was further investigated to measure its anti-biofilm potential and its effectiveness against methicillin-resistant Staphylococcus aureus strains. A structure-activity relationship study of the synthesized molecules led to the recognition of some important structural requirements for the observed antibacterial activity. Molecular docking followed by molecular dynamics (MD) simulations identified the binding site of the active compound FtsZ, a key protein in bacterial cell division, and the mechanism of action, i.e., the inhibition of its polymerization. The overall results may pave the way for a further rational development of isatin hybrids as FtsZ inhibitors, with a broader spectrum of activity against human pathogens and higher potency.